(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The pink market is gaining visibility exponentially, as it represents a high economic and attractive potential for companies, which implement marketing strategies to be attractive to this market. Therefore, this research seeks to know the perception that pink consumers have of the marketing strategies that companies deploy to capture them and satisfy their desires and needs. The research was quantitative, exploratory-descriptive and based on a non-probabilistic snowball sampling, with the participation of 234 students from the Universidad Juárez Autónoma de Tabasco who self-identified as part of the LGBTTTIAQ+ group. The conclusions of the study show that there is distrust to brands that target the pink market, perceiving them as an attitude of convenience and not for a real empathy, thus pink consumers tend to analyze and be alert about the actions that companies have with the community. Thus, most of them not only look at the products offered, but also at the actions and attitudes that companies have towards the LGBTTTIAQ+ community.